Changes of body composition in college female basketball players over approximately 6 months - Shiba, Junpei; Yamase, Hana (International Journal of Basketball Studies, 2023)
This study aimed to examine changes in 1) body composition among female college basketball players over approximately 6 months and 2) body composition by player position. In all, 10 female college basketball players were included (age: 19.2 ± 1.0 years, height: 162.9 ± 4.6 cm, Guards: n=3, Forwards: n=4, Centers: n=3). Measurements were taken at the following timepoints: the beginning of the in-season (In1: June), the middle of the in-season (In2: August), and the end of the in-season (In3: October). The body mass, percentage of body fat, body fat mass, and lean body mass (LBM) were recorded and analyzed. Significant differences were reported in the percentages of body fat (p = 0.004), and a significant trend was observed in body fat mass values between time points (p = 0.096). Post-test results showed a significant decrease and small effect size between In1 and In2 (p = 0.041, d = -0.21) and a significant decreasing trend (effect size, trivial) (p = 0.096, d = -0.11) between In1 and In3 in percentage of body fat. No significant differences were reported in the body fat mass values between time points. Among guard players, there were moderate and large decreases in the percentages of body fat between In1 and In2 and between In1 and In3, respectively (d = -1.20, d = -1.86). Further, moderate and large decreases in body fat mass were observed between In1 and In2 and between In1 and In3, respectively (d = -1.07, d = -1.51). Among center players, LBM showed small decreases between In1 and In3 and between In2 and In3 (d = -0.56, d = -0.58). Thus, resistance training may be necessary to prevent a decrease in LBM.